Clinical outcomes in unselected patients treated with the PROMUS Element platinum‐chromium, everolimus‐eluting stent: Final five‐year results from the PE PROVE Study. Issue 3 (20th October 2018) - Moreno, Raul; Legrand, Victor; Ferrario, Maurizio; MacCarthy, Philip; Redwood, Simon; Werner, Nikos; Jung, Werner; Ungi, Imre; Zaman, Azfar; Richardt, Gert; Crowley, James; Schwimmbeck, Peter; et al.
Abstract: Objectives: The goal of this analysis was to evaluate the final 5‐year safety and effectiveness of the PROMUS Element platinum‐chromium everolimus‐eluting stent in unselected patients treated in routine clinical practice. Background: The prospective, open‐label PROMUS Element™ European Post‐Approval Surveillance Study (PE‐PROVE) enrolled 1, 010 "real‐world" patients who received the PROMUS Element stent. Adverse event rates were low at 1‐year, and the incidence of stent thrombosis was 0.6%. Methods: The primary endpoint was target vessel failure (TVF; overall and PE stent‐related), a composite of cardiac death, myocardial infarction (MI) related to the target vessel, or target vessel revascularization (TVR) at 1‐year post‐implantation. Five‐year clinical outcomes were evaluated in overall as well as high‐risk patient subgroups. Results: The overall 5‐year TVF rate was 14.9%, with 7.0% being related to the study stent. Cardiac death, MI and TVR related to the study stent occurred in 0.5%, 3.2%, and 5.7%, respectively. Stent thrombosis through 5‐year follow‐up was 1.0%. The rates of overall and study stent related TVF were numerically higher in patients with medically treated diabetes, long lesions (≥28 mm), and small diameter vessels (≤2.5 mm) compared to the overall study population. Additionally, favorable stent thrombosis rates through 5 years were reported for the PROMUS Element stent in these high‐risk subgroups. Conclusions: The final 5‐year data from the PE‐PROVE study demonstrate favorable outcomes and low rates of adverse events with the PE stent when used in "real‐world" patients with coronary artery disease.